Torture, Livelihoods and Rehabilitation - Herbert, Tania Louise (Torture Journal, 2024)
The understanding of torture has evolved to encompass a complex interplay of factors including poverty, politics, health and psychosocial factors which increase vulnerability to torture. While torture remains a grave human rights violation, it is acknowledged as widespread and intertwined with broader human rights abuses. In response to this evolving understanding, rehabilitation efforts for torture survivors have expanded beyond medical and psychological care to encompass broader socio-economic dimensions, including livelihoods support. Livelihoods are not only a means of making a living, but also a source of purpose and identity. Where torture disrupts or destroys the assets, capabilities and supports that sustain livelihoods, the resulting suffering can be profound, particularly for individuals unable to flee or resettle. This article explores the intersect between livelihoods loss and torture, exploring where livelihoods loss co-occurs with torture, is a consequence of torture, or may be an act of torture in itself. The importance of documenting livelihoods losses in torture assessment and the integration of livelihoods into rehabilitation programs is considered. Programs must aim to restore sustainable and meaningful livelihoods whilst addressing inherent risks and limitations including the lack of capacity, expertise and resources of treatment centres. Although research in this area is sparse, existing evidence suggests that combining livelihoods rehabilitation with psychological and physical interventions, alongside long-term support are important components. For livelihood restoration to be effectively integrated, it must be survivor-centred, holistic, evidence-based and focused on safety. While the field is to date underexplored, this article provides a foundational framework for torture treatment centres and stakeholders to consider the role of livelihoods in both conceptualising and treating survivors of torture.